The Maapam Tradition in West Pasaman Community Life: A Study of Local Wisdom Values - Ayuthia Mayang Sari; Dina Rahma Dani (LP2M ISBI Bandung, 2026)
Maapam is a tradition of cooking apam carried out by the people of West Pasaman during certain religious moments, such as the month of Rajab coinciding with the Isra Mi'raj event, and the period leading to Ramadan. The tradition contains local wisdom values that are inherited across generations. This research aims to examine the cultural significance and educational value of the Maapam tradition using a qualitative method with an ethnographic approach. The results of the study show that Maapam functions as a cultural practice that combines social and spiritual dimensions. Horizontally, this tradition strengthens togetherness, mutual cooperation, solidarity, and intergenerational communication. Vertically, Maapam reflects on the strengthening of religious values through its relationship with religious momentum that is full of the meaning of worship and self-reflection. The values of piety, responsibility, and social concern contained in the Maapam traditions are relevant to the goals of national character education. Therefore, the Maapam tradition can be positioned as a contextual learning resource based on local wisdom that supports the Pancasila Student Profile Strengthening Project (P5) and the preservation of community cultural identity.